2017
DOI: 10.1021/acs.cgd.7b00213
|View full text |Cite
|
Sign up to set email alerts
|

The Plot Thickens: Gelation by Phenylalanine in Water and Dimethyl Sulfoxide

Abstract: Phenylalanine (Phe) is an amino acid of great interest as coupling of an aromatic group with a chiral hydrophilic region imparts a number of unique properties. Recently there has been an increased interest in the crystalline and gel forms of this compound, part as a result of the complex and undetermined structures of the resulting materials and the relationship of the solid forms of Phe with the disease phenylketonuria. In this report, we highlight the relationship between gelation, crystallization, and the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 51 publications
(155 reference statements)
3
37
0
Order By: Relevance
“…The self-associative binding modes of 1-31 weref irst explored within the solid state throught he use of single-crystal X-ray diffraction techniques. Crystal structures previously obtained for 8 and 16 show hydrogen bonded self-association through the formation of urea-anion tapes, [16] whilst 1,4,15,17,28,30,31 have been shown to dimerize through (thio)urea-anion hydrogen bond formation. [16,17] In contrast, ap revious structure obtained for 7 showed hydrogen bondeds elf-association throught he formation of urea-urea hydrogen bondedt apes.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…The self-associative binding modes of 1-31 weref irst explored within the solid state throught he use of single-crystal X-ray diffraction techniques. Crystal structures previously obtained for 8 and 16 show hydrogen bonded self-association through the formation of urea-anion tapes, [16] whilst 1,4,15,17,28,30,31 have been shown to dimerize through (thio)urea-anion hydrogen bond formation. [16,17] In contrast, ap revious structure obtained for 7 showed hydrogen bondeds elf-association throught he formation of urea-urea hydrogen bondedt apes.…”
Section: Resultsmentioning
confidence: 86%
“…Ac orrelation is alsoo bserved between CMC and compound counter cation (1,(8)(9)(10)(11). Here, theoreticalv alues of relative polarizability for those counter cations contained within the structures of 1, 8-11 werec alculated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Lloyd and co-workers reported the gelation of unprotected Phe in DMSO. [58] They found that Phe could form gels at a much lower concentration in DMSO, as compared to water. Noticeably, the DMSO gels were transparent, unlike the opaque hydrogels.…”
Section: Amino Acid Based Nanostructuresmentioning
confidence: 99%